A Study Of Determinants Of Entertaining Shopping - Sin, Chan Phooi (2008)
The present study, therefore, presents an investigation on the model of entertaining shopping experience developed by both Jones(1999) and Ibrahim (2002). The model will be examined by using shopping malls in Malaysia shoppers' entertaining shopping experience with the key factors to be focused in this study are retailer factors, customer factors, and transport or travel factors.